PENINGKATAN PEMAHAMAN MASYARAKAT DESA DRENGES KABUPATEN BOJONEGORO TENTANG PENGGUNAAN OBAT MELALUI PENYULUHAN PENGUNAAN OBAT YANG BENAR - Ilil Maidatuz Zulfa; Prasetyo Handrianto; Ratih Kusuma Wardani; Galuh Gondo Kusumo (Universitas Nahdlatul Ulama Sidoarjo, 2018)
Irrational drug use usually happens in self medication practise without any supervision from health care providers. Self medication practise usually does not consider the potential of allergic reaction, pregnancy, breast feeding, diet, and medication history.The promotion of rational drug use through communication, information, and education still need to be conducted to the community. This event is purposed to improve perception, knowledge, and attitude of Desa Drenges residents in the term of drug usage. A total 23 person of Desa Drengeswere enrolled in this eventfacilitated by village administrators.The perception, knowledge, and attitude of the residents recruited were evaluate through questionnaire filled before and after the event. The result showed the increase of perception, knowledge, and attitude of the residents up to 2,69%. From the result, The community service event can improve the quality of health of residents in Desa Drenges through the improvement of perception, knowledge, and attitude in the term of rational drug use.